Atomistic simulations of nanoscale crack-vacancy interaction in graphene. (December 2017) - Dewapriya, M.A.N.; Meguid, S.A.
Abstract: Linear elastic fracture mechanics establishes the conditions necessary for crack arrest by the introduction of a hole in its path. However, it is unclear how nanoscale crack-vacancy interaction manifests itself at the atomistic level. In this study, we employ molecular dynamics simulations to investigate the nanoscale crack-vacancy interaction in graphene by performing nanoscale uniaxial tensile test. Three aspects of the study are considered: (i) to create design envelopes to ascertain crack tip shielding zones (reduction in the stress field) and crack tip amplification zones (increase in the stress field) as a result of the presence of atomistic vacancies ahead of the crack tip, (ii) to examine the ability of the current system to arrest propagating cracks by the strategic placement of the nanoscale vacancies, and (iii) to investigate the crack healing phenomenon. Our results reveal that the nanoscale central crack can be arrested by the strategic positioning of symmetric nanoscale holes. Moreover, the presence of holes in close proximity to the crack tip leads to multiple stage crack growth involving both self-similar and crack branching. The study further reveals that the initially propagating cracks completely healed even though the applied tensile strain is not fully diminished. Graphical abstract: